Analysis of Wealth in Bulgaria According to Empirical Research - Peshev, Petar; Stefanova, Kristina; Bozhikin, Ivan (Research Papers, 2024)
This paper analyses wealth in Bulgaria according to estimates of its value, structure and distribution in selected scientific publications and databases, including data on wealth in Bulgaria from the World inequality database (WID); Global Wealth Report and Global Wealth Databook, published by Credit Suisse Research Institute; Allianz Global Wealth Report. The value, structure and distribution of wealth are analysed in static and dynamic terms, taking into account methodological assumptions, limitations and challenges of individual studies and methodologies. A distinction is made between the income capitalisation approach and the econometric estimation approach to derive values for wealth, its structure and distribution.
Keywords: Wealth; Distribution of wealth; Concentration of wealth; Top decile; Top percentile; Inequalities